1973
DOI: 10.1271/bbb1961.37.757
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Properties of Leucine Aminopeptidase I from Aspergillus oryzae

Abstract: An aminopeptidase from Aspergillus orvzae 460 was purified from the rivanol precipitable fraction. The partially purified enzyme was not homogeneous in disc electrophoresis, although symmetric profiles were obtained for enzyme protein and activity in Sephadex gel filtration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…On the other hand, at pH 4.0 the carboxypeptidase activities of A. oryzae extract were significantly greater than those of A. elegans extract and A. oryzae extract at pH 7.0, especially when the substrates were Z-Glu-Tyr (32.08 μmol/h/mL extract), Z-Leu-Tyr (21.33 μmol/h/mL extract), and Z-Ala-Leu (17.21 μmol/h/mL extract). These observations confirmed that A. oryzae has acidic carboxypeptidases, which is in agreement with earlier reports [17,[33][34][35]. The data presented here indicate that the carboxypeptidase activities in A. oryzae were higher when Tyr and Phe were at the C terminus than when Leu was at the C terminus.…”
Section: Specificity Of a Elegans Carboxypeptidasessupporting
confidence: 93%
“…On the other hand, at pH 4.0 the carboxypeptidase activities of A. oryzae extract were significantly greater than those of A. elegans extract and A. oryzae extract at pH 7.0, especially when the substrates were Z-Glu-Tyr (32.08 μmol/h/mL extract), Z-Leu-Tyr (21.33 μmol/h/mL extract), and Z-Ala-Leu (17.21 μmol/h/mL extract). These observations confirmed that A. oryzae has acidic carboxypeptidases, which is in agreement with earlier reports [17,[33][34][35]. The data presented here indicate that the carboxypeptidase activities in A. oryzae were higher when Tyr and Phe were at the C terminus than when Leu was at the C terminus.…”
Section: Specificity Of a Elegans Carboxypeptidasessupporting
confidence: 93%
“…A 1200 bp fragment containing the nucleotide sequence of the gene encoding an Aspergillus oryzae/Aspergillus sojae 31 kDa Lap (orLap1) (Nakadai et al, 1973;Chien et al, 2002;US Patent no. 5,994,113) was obtained by PCR of A. oryzae genomic DNA using the oligonucleotides 59-ATGCGTTTCCTCCCCTGCATCGCG-39 (sense) and 59-CAGCGAATCTGCGAAGGCAAGCTC-39 (antisense).…”
Section: Cloning Of Genes Encoding T Rubrum and A Fumigatus Lapsmentioning
confidence: 99%
“…e e, Cbz-Glu-Tyr; ° 0, Cbz-Glu-Phe; Effect of pH on Acid Carboxypeptidase IV.Peptidase activity was assayed after 20 min incubation at 30'C with four different peptides. 0.05 M CH 3 COONa-HCI buffer ( ) and 0.05 M acetate buffer (---) were used 6. 6, Cbz-Gly-Pro-Leu-Gly; ° 0, Aoc-Gln-LeuGly;.…”
mentioning
confidence: 99%